The Effect of Hand Reaction Speed and Wrist Flexion on Short-Service Ability in Badminton Games - Sahabuddin Sahabuddin (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study aims to determine: (1) The effect of hand reaction speed on short serve ability in badminton games; (2) the Effect of wrist flexibility on short serve ability in badminton games; and (3) the Effect of hand reaction speed and wrist flexibility on short serve ability in badminton games. The population of this study were all students of SMA Negeri 5 Soppeng with a total sample of 30 students selected by random sampling. The data analysis technique used is the descriptive analysis technique, data normality test, data linearity test and regression analysis using the SPSS program. The research results show that; (1) There is an effect of hand reaction speed on short serve ability in badminton games of 68.6%; (2) There is an effect of wrist flexibility on short serve ability in badminton games of 55.4%; and (3) There is an effect of hand reaction speed and wrist flexibility on short serve ability in badminton game of 86.1%.